2021
DOI: 10.3390/en14040906
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Modeling of Sand Production Using Coupled DEM-LBM

Abstract: Sand production is a complex phenomenon caused by the erosion of borehole walls during the extraction of hydrocarbons. In this paper, the sanding process in a typical Thick-Walled Hollow Cylinder (TWHC) test is numerically simulated. The main objective of the study is to model the particulate mechanism of sand production in granular assemblies with different bonding conditions and examine the effects of parameters such as stress level and cavity size on the sanding model. Due to the discrete nature of sand par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…To this end, we deduce empirical values for the sand production coefficient λ 2 by best fitting the experimental data of 12 with numerical simulations. The results show that λ 2 does indeed have a fairly smooth dependence on the external conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we deduce empirical values for the sand production coefficient λ 2 by best fitting the experimental data of 12 with numerical simulations. The results show that λ 2 does indeed have a fairly smooth dependence on the external conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sand production, can be quantified by a volume of produced solids against time graph, exhibiting the physical response of the rock under given external stress and flow conditions. [7][8][9][10][11][12] Papamichos et al, in (2001) 13 claimed, through laboratory experiments on hollow cylinder tests, that plastic yielding is the cause of micro-cracks, resulting from the application of external loads, which may serve as erosion starting points. However, this statement was challenged by other investigators by conducting experiments under true triaxial stress state on cubic samples which have shown that yielding of the material around the wellbore surface is not necessarily an indicator for on-setting sand production.…”
Section: Introductionmentioning
confidence: 99%
“…Also, can be used to study the basic mechanism of sand production on an experimental scale (Ghassemi and Pak, 2015;Han and Cundall, 2017) and analyze the permeability before and after sand production and the evolution process of the complex force chain network inside the model (Xia et al, 2022). On the basis of predecessors, Honari et al simulated different stages of sand production by integrating Immersion Moving Boundary (IMB) method, including scale effect, extension of failure zone under incremental stress, and stress change during particle erosion (Honari and Hosseininia, 2021). The study believed that the smaller the pore diameter and the greater the stress value, the easier the sand production.…”
Section: Coupled Lattice-boltzmann and Methoddiscrete Element Methodsmentioning
confidence: 99%
“…where ߩ is the fluid density, u is the fluid velocity, and ‫‬ is the fluid pressure. To calculate the flow, the lattice Boltzmann method is adopted [13][14][15][16][17][18][19][20][21][22][23][24], whose evolution equation is…”
Section: Methodsmentioning
confidence: 99%